Characterizing Atrazine Degradation by Molybdenum-reducing Pseudomonas sp. (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
The most feasible and economical technique for removal of toxic compounds in the polluted environment is bioremediation. This technique surpasses other physicochemical methods in recent time for being effective particularly at a lower concentration of the toxicant. In this study, seven (7) previously isolated molybdenum-reducing bacteria were screened for their potential to degrade atrazine herbicide as sole carbon source for growth. Bacterial colony count on mineral salt medium supplemented with atrazine was used for the screening, while the effects of incubation time, concentration, temperature, pH, inoculum size and heavy metals on atrazine biodegradation was used in characterizing the candidate isolate. Of the seven isolates, an isolate identified as Pseudomonas sp. that grew best with a count of 195 CFU/mL was chosen. The optimum conditions supporting atrazine degradation by Pseudomonas sp. were found to be temperature 35 °C, pH 7.0, incubation time 48 hours and 400 µL inoculum. The use of atrazine as carbon and electron donor source for molybdenum reduction, poorly support molybdenum blue (Mo-blue) production. At a concentration (2 ppm), heavy metals such as lead and copper did not significantly (p>0.05) affect atrazine biodegradation relative to control, iron and silver shows a relative stimulatory effect to the process, while mercury and zinc showed significant (p